Teacher Empowerment Strategies: Reasons for Nonfulfillment and Solution Suggestions - Naciye ÇALIŞICI ÇELİK; Bilgen KIRAL (Anı Publishing, 2022)
This research was carried out to determine the empowerment strategies school principals should implement and the reasons for not being empowering. It was conducted with four elementary school teachers and four school principals in a city in the Aegean Region in the 2017-2018 academic year. In the study, descriptive phenomenology design, one of the qualitative research designs, was used. According to the results, it was revealed that the empowerment strategies to be implemented by school principals were classified under the categories of physical and psychological support, communication, school functioning, and teacher autonomy. The reasons for not making teacher empowerment by school principals were determined as personal, administrative, financial, and limited authority reasons. What the Ministry of National Education should do for teacher empowerment was revealed. They should adopt policies that support personal development and teacher autonomy, increase the authority of school principals, and make changes in the legislation. Following the findings, various suggestions were made on such issues as increasing financial resources that hinder empowerment.